2021
DOI: 10.1002/oby.23318
|View full text |Cite
|
Sign up to set email alerts
|

Intervening on exercise and daylong movement for weight loss maintenance in older adults: A randomized, clinical trial

Abstract: Objective This study aimed to determine the impact of dietary weight loss (WL) plus aerobic exercise (EX) and a “move more, more often” approach to activity promotion (SitLess; SL) on WL and maintenance. Methods Low‐active older adults (age 65‐86 years) with obesity were randomized to WL+EX, WL+SL, or WL+EX+SL. Participants received a social‐cognitive group‐mediated behavioral WL program for 6 months, followed by a 12‐month maintenance period. EX participants received guided walking exercise with the goal of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Of 57,721 unique records, 109 articles of 54 studies were included in the evidence map as they provided information on outcomes assessed (Figure 1 and Table S4). 34–87 The unique accession numbers from all database searches are available upon request.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 57,721 unique records, 109 articles of 54 studies were included in the evidence map as they provided information on outcomes assessed (Figure 1 and Table S4). 34–87 The unique accession numbers from all database searches are available upon request.…”
Section: Resultsmentioning
confidence: 99%
“…No study in individuals with SO lasted longer than 26 weeks. Seven studies, all in individuals of the obesity phenotype, included a post‐intervention follow‐up period ranging from 5 to 19 months for at least some study outcomes 45,57,63,64,70,76,81 . The study's participants' age ranged from 65.3 to 77.4 years across studies, with only four RCTs reporting a mean age of 75 years and older.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, low levels of physical activity, and thus high sedentary time, has been shown to be related to hedonic eating 60 . Studying older adults in a weight regain study, we recently found that coupling of a SitLess intervention with weight loss was superior to exercise with weight loss in curbing 12‐month weight regain following an intensive 6‐month program of weight loss 61 . Because the SitLess intervention involved movement across the day, an important question for future study is how the distribution of movement across the day may influence neural networks involved in hedonic eating.…”
Section: Moderating Influences On Neural Vulnerabilitiesmentioning
confidence: 99%